(untitled) (Proceedings of International Conference on Special Education, 2023)
Teaching strategies that can be used in teaching prepositions in early childhood education (ECE) learners with autism spectrum disorder (ASD). Using a qualitative narrative research design, accounts from teachers who teach prepositions to early childhood education learners with ASD in selected private schools in Metro Manila were collected to identify specific teaching strategies utilized in classrooms. It is imperative to teach prepositions to ECE learners with ASD, as it accounts for the improvement of adaptive skills including navigating, doing spatial tasks, locating the placement of an object or person, and improving communication skills. Semi-structured interview questions were prepared before the one-on-one interview sessions with the teachers. Findings show that the use of visual aids, repetition, and a naturalistic approach are the most utilized strategies used in teaching prepositions to ECE learners with ASD. Teacher collaboration and the present level of performance of the child are the basis for the implementation of the teaching strategies. Research in teaching essential concepts of the English language to learners with additional needs is necessary to bridge the gap between teaching strategies and learners’ acquisition of knowledge.